The Adventures of Matter (and of Form): Glauco Gresleri and Modern Eclecticism - Marco Ferrari (In_Bo, 2019)
The small and remote village of Vajont is a very important place in order to understand the complex cultural and poetic dimension of Glauco Gresleri’s work. For those who visit the cemetery with the chapel and the church with the parish buildings it is impossible to imagine how the two projects – both designed in partnership with Silvano Varnier – belong to the same architect. It is evident how the radical differences of the two contexts – the open and rough landscape in one case, the rigidity of the urban grid on the other – have played a crucial role in determining their different characters: organic and with a material aspect the first, geometric and almost abstract the second. However it is equally evident that this can not be the only reason. From a linguistic point of view, what Gresleri displays, in these two coeval works, is a real programmatic opposition and, after all, a disenchanted declaration of eclecticism. The latter, more than the many others that can be found postwar (especially in Italy), arises from the construction aspect of the architecture and, in particular, from the relationships with the physical and conceptual characters of the material. A composite, manifold, and versatile attitude that still questions us and poses problems of great critical importance, useful to further articulate the many, possible stories of the Modern, in Italy and abroad.